Factors influencing purchasing intention towards organic foods among UPM students - Ying, Yan Sia; Lau, Jasmine Leby (Malaysia Consumer And Family Economy Association (MACFEA), 2023)
This study aims to determine the factors influencing the purchase intention towards organic food among University Putra Malaysia (UPM) students. This study randomly selected five faculties from 14 faculties located at the main campus in UPM. This study collected 200 respondents through multistage sampling and applied questionnaires as research instruments. Data were analyzed using Statistical Package for Social Science (SPSS) for Windows version 28.0. Pearson Correlation Coefficients showed that attitude, subjective norm, perceived behavioral control, and health consciousness were significantly related to the purchase intention towards organic food among UPM students. Multiple Linear Regression analysis showed that attitude, subjective norms, and perceived behavioral control greatly influence the purchase intention towards organic food among UPM students. This study implies that it has extended the knowledge of the Theory of Planned Behavior concepts related to purchase intention.